Anti-TNF alpha therapy of rheumatoid arthritis: what have we learned? - Feldmann, M; Maini, R (2001)
Rheumatoid arthritis (RA), a systemic disease, is characterized by a chronic inflammatory reaction in the synovium of joints and is associated with degeneration of cartilage and erosion of juxta-articular bone. Many pro-inflammatory cytokines including TNF alpha, chemokines, and growth factors are expressed in diseased joints. The rationale that TNF alpha played a central role in regulating these molecules, and their pathophysiological potential, was initially provided by the demonstration that anti-TNF alpha antibodies added to in vitro cultures of a representative population of cells derived from diseased joints inhibited the spontaneous production of IL-1 and other pro-inflammatory cytokines. Systemic administration of anti-TNF alpha antibody or sTNFR fusion protein to mouse models of RA was shown to be anti-inflammatory and joint protective. Clinical investigations in which the activity of TNF alpha in RA patients was blocked with intravenously administered infliximab, a chimeric anti-TNF alpha monoclonal antibody (mAB), has provided evidence that TNF regulates IL-6, IL-8, MCP-1, and VEGF production, recruitment of immune and inflammatory cells into joints, angiogenesis, and reduction of blood levels of matrix metalloproteinases-1 and -3. Randomized, placebo-controlled, multi-center clinical trials of human TNF alpha inhibitors have demonstrated their consistent and remarkable efficacy in controlling signs and symptoms, with a favorable safety profile, in approximately two thirds of patients for up to 2 years, and their ability to retard joint damage. Infliximab (a mAB), and etanercept (a sTNF-R-Fc fusion protein) have been approved by regulatory authorities in the United States and Europe for treating RA, and they represent a significant new addition to available therapeutic options.